A THE EMPOWERMENT OF COMMUNAL AND SOCIO-CULTURAL VALUE IN PYRAMID SCHEME DISPUTE SETTLEMENT - Tuti Rastuti; Utari Dewi Fatimah; Ghandhi Pharmacista (SAMPURASUN, 2018)
Due to the unlawful practice of pyramid scheme business, there has been noticeable damage on communal value and living law within the affected communities. This condition becomes the source of dispute and affects the loss of trust, harmony and the damage of social and communal order. The segregated litigation process, which is the most common solution; could not solve the complex nature of the dispute. Therefore, there should be a new comprehensive alternative to restore both financial loss and the damage within the affected communities. The research aims to study the use of communal and socio-cultural value in the settlement of Pyramid scheme dispute, which is not only vulnerable as the modus of the scam but also as the solution for the victims. The method used is juridical empiric with juridical normative approach. The research shows the analysis of legal framework to solve the conflict within the community caused by pyramid scheme progressively. The research indicates that penal mediation could be the solution of the problem. The research outcomes could contribute to the alternative to settle the dispute, also to restore the social order and to restore the loss accordingly.